High intensity interval training for patients with hypertension: A scoping review - Miftahurrizqia, Erika; Rahman, Farid (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Hypertension is a major risk factor worldwide for cardiovascular disease (CVD), stroke, disability, and death. Lack of physical activity is one of the main factors causing the increasing prevalence of hypertension. High-intensity interval training (HIIT) has been shown to be effective in reducing blood pressure levels in people with hypertension. Purpose: To evaluate high intensity interval training for patients with hypertension. Method: Scoping review using PRISMA guidelines in identifying 7,654 articles. Article collection was conducted by systematic search on Google Scholar, PubMed, ScienceDirect, Taylor & Francis Online, Nature, and Wiley Online Library databases published from 2013-2024. Results: Thirty articles used in the inclusion selection showed the effect of high intensity interval training on hypertension sufferers, and was proven to cause a decrease in blood pressure levels in hypertension sufferers. Conclusion: Shows that HIIT is effective in reducing blood pressure in various types of hypertension, from types I and II to arterial at the age of 16-70 years. Keywords: Blood Pressure; High Intensity Interval Training; Hypertension. Pendahuluan: Hipertensi merupakan faktor risiko utama di dunia untuk cardiovascular disease (CVD), stroke, kecacatan, dan kematian. Kurangnya aktivitas fisik menjadi salah satu faktor utama penyebab meningkatnya prevalensi hipertensi. High intensity interval training (HIIT) terbukti efektif dalam mengurangi kadar tekanan darah pada penderita hipertensi. Tujuan: Untuk mengevaluasi latihan interval intensitas tinggi untuk pasien hipertensi. Metode: Scoping review menggunakan panduan PRISMA dalam mengidentifikasi 7.654 artikel. Pengumpulan artikel dilakukan dengan pencarian sistematis pada database Google Scholar, PubMed, ScienceDirect, Taylor & Francis Online, Nature, dan Wiley Online Library yang diterbitkan dari tahun 2013-2024. Hasil: Tiga puluh artikel yang digunakan dalam seleksi inklusi menunjukkan pengaruh high intensity interval training pada penderita hipertensi dan terbukti dapat menyebabkan turunnya kadar tekanan darah pada penderita hipertensi. Simpulan: Menunjukkan bahwa HIIT efektif menurunkan tekanan darah pada berbagai jenis hipertensi, dari tipe I dan II hingga arteri pada usia 16-70 tahun. Kata Kunci: High Intensity Interval Training; Hipertensi; Tekanan Darah.